CANONICAL STRUCTURE OF GAUGE INVARIANCE PROCA'S ELECTRODYNAMICS THEORY - Zambrano, German E. R. (2018)
Proca's electrodynamics describes a theory of massive photons which is not gauge invariant. In this paper we show that the gauge invariance is recovered if a scalar field is properly incorporated into the theory. We followed the Dirac's technique to perform a detailed analysis of the constraint structure of the theory. Appropriate gauge conditions were derived to eliminate the first class constraints and obtain the Dirac's brackets of the independent dynamical variables. Alternatively, the generalized symplectic formalism method is used to study the gauge invariance Proca's electrodynamics theory. After fixing the gauge, the generalized brackets are calculated and the equivalence with the Dirac's brackets is shown.